Criminal and legal characteristics of rape - Shvanskaia V. D. (Science, education, society: trends and prospects, 2019)
In the article, the author considers the criminal law characteristics of rape, as well as analyzes the legislation in the field under study and reveals the criminal liability for these crimes. The author explores judicial practice regarding dangerous crimes against the individual.
Keywords: преступление; уголовная ответственность; crime; изнасилование; criminal liability; rape; принудительное половое сношение; forced sexual intercourse